Mindnet: Acquiring And Structuring Semantic Information From Text - Richardson, Stephen D.; Dolan, Bill; Vanderwende, Lucy (COLING-ACL 1998, 1998)
As a lexical knowledge base constructed automatically from the definitions and example sentences in two machine-readable dictionaries (MRDs), MindNet embodies several features that distinguish it from prior work with MRDs. It is, however, more than this static resource alone. MindNet represents a general methodology for acquiring, structuring, accessing, and exploiting semantic information from natural language text. This paper provides an overview of the distinguishing characteristics of MindNet, the steps involved in its creation, and its extension beyond dictionary text.